2022
DOI: 10.3390/ijms23158522
|View full text |Cite
|
Sign up to set email alerts
|

High-Light-Induced Degradation of Photosystem II Subunits’ Involvement in the Albino Phenotype in Tea Plants

Abstract: The light-sensitive (LS) albino tea plant grows albinic shoots lacking chlorophylls (Chls) under high-light (HL) conditions, and the albinic shoots re-green under low light (LL) conditions. The albinic shoots contain a high level of amino acids and are preferential materials for processing quality green tea. The young plants of the albino tea cultivars are difficult to be cultivated owing to lacking Chls. The mechanisms of the tea leaf bleaching and re-greening are unknown. We detected the activity and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…However, numerous DEGs belonged to the photosynthesis-related pathways although the content of photosynthetic pigments also increased in the shaded leaves of ‘HJY’ [ 8 ]. Furthermore, high light exposure had been found to accelerate the depolymerization of PSII complex subunits such as CP43, CP47, PsbP, and PsbR, resulting in the degradation of the reaction center proteins D1 and D2 [ 13 ]. These findings suggested that the albino phenotype of tea plants might be closely associated with the abnormal assembly of the photosynthesis-related proteins in addition to the lack of pigments [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous DEGs belonged to the photosynthesis-related pathways although the content of photosynthetic pigments also increased in the shaded leaves of ‘HJY’ [ 8 ]. Furthermore, high light exposure had been found to accelerate the depolymerization of PSII complex subunits such as CP43, CP47, PsbP, and PsbR, resulting in the degradation of the reaction center proteins D1 and D2 [ 13 ]. These findings suggested that the albino phenotype of tea plants might be closely associated with the abnormal assembly of the photosynthesis-related proteins in addition to the lack of pigments [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar inhibition of the chlorophyll biosynthesis had also been witnessed in light-sensitive albino cultivars ‘Zhonghuang 2#′ [ 11 ]. In the albino leaves of the ‘Huangjinya’, the expressions of the genes encoding the photosystem II (PSII) complex subunits and light-harvesting complex (LHC) subunits were remarkably suppressed [ 7 ], which would inhibit the accumulation of the CP43 and CP47, consequently accelerate the degradation of D1 and D2 [ 13 ], and finally induce the collapse of photosynthesis. Comparison between the albino leaves and re-greened ones of the ‘Huangjinya’ showed that the differentially expressed genes (DEGs) were highly enriched in the pathways of photosynthesis and the photosynthetic antenna proteins [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually it leads to a decrease in chlorophyll concentration or the albino phenotype. Interestingly, these processes are reversible, and it leads to adaptations to high-light stress in the etiolated tea mutant [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study noted that using the second, fifth and last amino acids of the PPR motif to predict downstream target sequences containing RNA editing sites would obtain more accurate results [ 51 ]. An absence of RNA editing can cause albino leaves and etiolation in some Arabidopsis and rice mutants, such as atclb19 , osppr6 , osdua1 and atgun1 [ 12 , 13 , 30 , 52 ], and many albino and etiolation varieties of tea plants have been bred [ 32 ], such as Baiye 1, Huabai 1, Huangjinya, etc. However, whether the extent of RNA editing is affected by the color change of tea leaves remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In China, many albino and etiolation tea cultivars, such as ‘Baiye 1’, ‘Huangjinya’, ‘Huabai 1’ and ’Baijiguan’ [ 32 , 33 , 34 ], attract more attention due to their umami taste, lower astringency and higher economic and ornamental value [ 35 ]. Numerous studies reported that loss of the RNA editing function could lead to changes in plant leaf color [ 12 , 30 ].…”
Section: Introductionmentioning
confidence: 99%